The study of emoji linguistic behaviour: an examination of the theses raised (and not raised) in the academic literature - Ferrari Nieto, Enrique (Communication & Society, 2023)
This bibliographic review of academic research on emoji reveals how the bulk of studies accepts it as a language but do not develop detailed linguistic analysis that could support this claim: they accept the clues provided by the initial studies, as if the scientific community had already reached such a consensus. However, the truth is that the fields in which emoji have generated the greatest academic interest (computer science, psychology and cognitive science) have considered the study of their linguistic nature a minor issue. Therefore, research on emoji has been growing over the years, widening the scope of its contributions, but with a common core made up of few basic notions about its linguistic condition that has important blind spots, in which Linguistics hasn’t done (generally) its work to place it in this new context for communication that the digital environments represent, despite the supports provided by multimodality and visual language theory. From these two disciplines, some authors have boldly suggested the emoji’s status as a gesture. However, to analyse its linguistic nature and behaviour, it is more accurate to understand the emoji, not as a gesture, but as a simplified representation of a gesture, without the unique features that a personal gesture has. The emoji seems to be the tool that, with fewer resources, best ensures that the interlocutor can understand the intentionality with which the sender has written the message.
Keywords: emoji; gesture; Linguistics; literature review; multimodality; Scopus; WOS